SOCIOLOGICAL APPROACH TO THE STUDY OF THE LEGAL CULTURE OF THE POPULATION: VALUE ASPECT - KATKOVA L.V.; MEKKA O.A. (Legal Bulletin)
The relevance of the research topic is due to the need to take into account in the process of studying legal culture its various modifications and manifestations determined by the characteristics of real carriers of political and legal culture in the form of social groups and strata of society. Since the political and legal culture is understood as a normative value system, it is necessary to analyze the concepts typical for the expression of its basic values. As such, the authors consider the concepts of “freedom”, “justice”, “equality”. But historically, different subjects put different meanings into these concepts. Explication of these concepts makes it possible to concretize the content of the phenomenon of legal culture in modern Russian society and its various modifications, taking into account social stratification. The main goal of the article is to analyze the content of the categories “freedom” and “justice” in relation to various modifications of legal culture. The problems under consideration. A common problem is the lack of knowledge about empirical indicators that are appropriate to use in research tools to fix different types of political and legal culture of the population. For this purpose, the article examines the connotations of the concepts of “freedom” and “justice”. The methods used. Along with the general scientific systematic method of analyzing legal phenomena, private scientific methods (sociological and axiological), as well as the method of legal hermeneutics were used in the preparation of the article.